The Role of the Law on Electronic Information and Transactions in Overcoming Challenges of Democracy in Indonesia - et. al, Ahmad Tholabi Kharlie (International Journal of Advanced Science and Technology, 2019)
Abstract: Democracy is idealized as a government system that provides space for citizens to be freely involved in the governance process. This space can be in the form of freedom of opinion and expression. However, the concept of freedom found in democracy often gives birth to a number of issues and paradoxes that have the potential to threaten the sustainability of democracy itself, such as the potential for the emergence of social conflict, social disintegration, segregation politics, and negative excesses as the result of the strong identity politics. The presence of the Law on Electronic Information and Transactions (EIT Law) has a strategic role in safeguarding the future and to face challenges of democracy in Indonesia by applying restrictions to the concept of freedom. This is in line with efforts to realize the principle of democratize rechstaat (democracy within the state of law) that seeks to implement democracy on the social order for the citizens. This article focuses on the analysis of the role of Law No.11 of 2008 concerning Electronic Information and Transactions as one of the legal instruments that strives for the realization of social order in the implementation of democracy to minimize the emergence of democratic paradoxes by analyzing the application of the law as this paper’s research method. This article is expected to provide a new perspective on the importance of implementing the legal instrument in the form of EIT Law to realize the concept of democratize rechstaat in Indonesia.